Probing the Structure of Quantum Mechanics : Nonlinearity, Nonlocality, Computation and Axiomatics. - Aerts, Diederik (World Scientific Publishing Company, 2002)
During the last decade, scientists working in quantum theory have been engaging in promising new fields such as quantum computation and quantum information processing, and have also been reflecting on the possibilities of nonlinear behavior on the quantum level. These are challenging undertakings because (1) they will result in new solutions to important technical and practical problems that were unsolvable by the classical approaches (for example, quantum computers can calculate problems that are intractable if one uses classical computers); and (2) they open up new 'hard' problems of a funda.